Controlled pVEGF delivery via a gene-activated matrix comprised of a peptide-modified non-viral vector and a nanofibrous scaffold for skin wound healing. (1st March 2022) - He, Shan; Fang, Ju; Zhong, Chuanxin; Ren, Fuzeng; Wang, Min
Abstract: Regulating cell function and tissue formation by combining gene delivery with functional scaffolds to create gene-activated matrices (GAMs) is a promising strategy for tissue engineering. However, fabrication of GAMs with low cytotoxicity, high transfection efficiency, and long-term gene delivery properties remains a challenge. In this study, a non-viral DNA delivery nanocomplex was developed by modifying poly (D, L-lactic-co-glycolic acid)/polyethylenimine (PLGA/PEI) nanoparticles with the cell-penetrating peptide KALA. Subsequently, the nanocomplex carrying plasmid DNA encoding vascular endothelial growth factor (pVEGF) was immobilized onto a polydopamine-coated electrospun alginate nanofibrous scaffold, resulting in a GAM for enhanced skin wound healing. The nanocomplex exhibited much lower cytotoxicity and comparable or even higher transfection efficiency compared with PEI. The GAM enabled sustained gene release and long-tern transgene expression of VEGF in vitro . In an excisional full-thickness skin wound rat model, the GAM could accelerate wound closure, promote complete re-epithelization, reduce inflammatory response, and enhance neovascularization, ultimately enhancing skin wound healing. The current GAM comprising a low-toxic gene delivery nanocomplex and a biocompatible 3D nanofibrous scaffold demonstrates great potential for mediating long-term cell functions and may become a powerful tool for gene delivery in tissue engineering. Statement of significance: Gene delivery is a promising strategy in promoting tissue regeneration as an effective alternative to growth factor delivery, but the study on three-dimensional gene-activated scaffolds remains in its infancy. Herein, a biodegradable nanofibrous gene-activated matrix integrating non-viral nanoparticle vector was designed and evaluated both in vitro and in vivo . The results show that the nanoparticle vector provided high transfection efficiency with minimal cytotoxicity. After surface immobilization of the nanocomplexes carrying plasmid DNA encoding vascular endothelial growth factor (pVEGF), the nanofibrous scaffold enabled sustained DNA release and long-term transgene expression in vitro . In a rat full-thickness skin wound model, the scaffold could accelerate wound healing. This innovative gene-activated matrix can be a promising candidate for tissue regeneration. Graphical abstract: Image, graphical abstract